Pengaruh Ukuran Perusahaan, Komite Audit, Pertumbuhan Penjualan, dan Kepemilikan Asing Terhadap Penghindaran Pajak dengan Tingkat Implementasi IFRS sebagai Moderasi - Eka Ismiyanti; Ahalik (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study uses a research model to obtain empirical evidence about the effect of company size, audit committee, sales growth, and foreign ownership on tax avoidance with the level of IFRS implementation as a moderating variable. The variables used in this research model are company size, audit committee, sales growth, foreign ownership, tax avoidance, and the level of IFRS implementation. The population of this study is companies registered in the Kompas 100 index in the period 2016 - 2018. Based on sampling using the purposive sampling method, the samples used in this study were 52 companies with a period of 3 (three) years producing 156 total observations. Data analysis was performed with descriptive statistical analysis, and Moderated Regression Analysis (MRA) with SPSS version 25. The results of the study concluded that company size and foreign ownership had no effect on tax avoidance, the audit committee and sales growth had an effect on tax avoidance. The level of IFRS implementation is not able to moderate either the influence of company size, audit committee, sales growth and foreign ownership on tax avoidance.